Understanding Purchase Intention Towards Imported Products: Role of Ethnocentrism, Country of Origin, and Social Influence - Gantulga, Urandelger; Ganbold, Munkhbayasgalan (Jurnal Ilmiah Peuradeun, 2022)
The previous research was mainly focused on consumers' purchase intention toward imported products in developed countries, whereas there is insufficient research conducted in developing countries like Mongolia. Therefore, the current study analyzed consumers' purchase intention toward imported products. We specifically examine the effects of the country of origin (COO), Ethnocentrism, and social influence on imported products' purchase intention through the product image and quality mediation role. To achieve the purpose of the research, an online survey was conducted on four hundred twenty-six Mongolian female consumers who experienced purchasing imported handbags. We used SPSS 23 and PLS-SEM software to test hypotheses. Moreover, we explored that an individual's perception of social influence was essential in purchasing imported products. Individuals with a higher degree of social influence prefer to buy imported products, e. g., and handbags, without a prior evaluation. Implications of the findings for theory and managerial practice are discussed, and future research directions are identified.